Uncovering Workplace Dynamics from their Impact on Job Satisfaction: Mengungkap Dinamika di Tempat Kerja dari Dampaknya terhadap Kepuasan Kerja - Ferdi Rahmad Irawan; Herlinda Maya Kumala Sari (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the relationship between workplace conflict, job stress, compensation, and job satisfaction within PT Otsuka Indonesia Distribution. Using quantitative methods and data from 101 employees, findings reveal that workplace conflict and job stress negatively impact job satisfaction, while compensation has a positive effect. These factors collectively influence job satisfaction, highlighting the importance of addressing workplace dynamics for organizational success. Highlight: Quantitative analysis: Conflict, stress, compensation's impact on job satisfaction. Conflict, stress reduce; compensation boosts job satisfaction. Understanding key factors vital for organizational success and employee well-being. Keyword: Konflik di Tempat Kerja, Stres Kerja, Kompensasi, Kepuasan Kerja, Analisis Kuantitatif